Meningkatkan Minat Membaca Siswa Sd N 2 Gadingsukuh Kelas Ii Menggunakan Metode Struktural Analitik Sintetik (Sas) - Khasanah, Solikhati (Prosiding University Research Colloquium, 2021)
This study aims to increase interest in reading by using the SAS method in second grade students of SD Negeri 2 Gadingsukuh. This research was conducted using classroom action research. The subjects of this research were second grade students of SD Negeri 2 Gadingsukuh Semester II for the 2020/2021 Academic Year, totaling 10 students. In this study using the SAS method. The techniques used in this research are: 1) scale, 2) observation, and 3) documentation. The data analysis technique used descriptive, quantitative, and qualitative analysis. The results of the study indicate that the reading interest of the second grade students of SD Negeri 2 Gadingsukuh can be increased by using the SAS method. In the pre-action, the percentage of students who have a minimum amount of reading interest has reached a good predicate of 0%. In the first cycle the number of students who have reached an average value of 61. In the second cycle the number of students who have achieved an increase with an average value of 79. Learning using the SAS method has increased in the second cycle.